Application of Titanium-Silica-Graphite Composite Material for Photocatalytic Process of Methylene Blue - Lia Destiarti; Risya Sasri (Indonesian Journal of Chemistry, 2020)
The use of TiO2 in the slurry system for the photocatalytic process has disadvantages. It causes the resistance of UV transmission because it is cloudy and the difficulty for obtaining the catalyst at the end of the process. Therefore, an attempt to overcome this was conducted by compositing TiO2 on SiO2. Furthermore, carbon material can be used as a support material for TiO2-SiO2, so that the mixed materials can be used as a photocatalyst. The methods for synthesis the material was a sol-gel method by varying the composition of TiO2-SiO2/graphite, which was 1:1; 1:2; and 2:1. The material obtained was characterized by FTIR, DRUV, XRD, and SEM. Photocatalytic activity of the synthesized material was tested in methylene blue solution whereas the quantitative data derived from UV-Vis spectrometry measurement. Photocatalyst activity was carried out by varying the degradation time of 30–180 min. The FTIR spectrum showed that O-H (~3400 cm–1) and C-O (~1100 cm–1) are the major groups in the synthesized materials. The value of bandgap energy (Eg) were 4.15, 4.20, 5.22, and 5.19 eV for TiO2-SiO2, TiO2-SiO2/G (1:1; 1:2; and 2:1) composites, respectively. The XRD pattern of TiO2-SiO2 showed that the highest peaks of 2q were observed at 25.32, 37.71 and 47.91°. Graphite identity appeared at 2q = 59.87°. Micrograph of SEM showed a homogenous dispersion of spherical particles in the materials. Photocatalytic test results showed that TiO2-SiO2/G with a composition of 2:1 has the highest percentage of methylene blue degradation, which reached 94% at 180 min.